Práticas psicológicas na atenção básica: vivências de psicólogos que atuam em residência multiprofissional em saúde - Rodrigues, Patrícia Matte (2017)
Some studies indicate a misbalance between the practices developed by primary health care psychologists and the specific demands of this context. Those studies point out to a mere transposition of the traditional model of clinic, without the proper contextualization that this area requests, besides some difficulties in teamwork. Thus, it is understood that psychology faces a challenge in qualifying its training in order to perform accordingly to the principles of the Brazilian Health Care System (SUS). Towards this challenge, psychology has found in the Multiprofessional Residencies in Health Care an opportunity of a training, which is diverse from that offered in undergraduate courses, that aims to qualify its practices for the work in public health care. Based on that, this research aimed to acknowledge the professional practices of psychologists who are part of a Multiprofessional Residency in Health Care Program, in the context of primary health care. Therefore, it was conducted a qualitative and exploratory research. The data collection was performed with semi-structured interviews. After the transcription of the interviews, data analysis followed the content analysis technique. The participants were eight psychology residents in the programs of Multiprofessional Residency Programs of two higher education institutes, from the city of Porto Alegre, Brazil. The results were discussed in three articles. The first article discussed the value granted to the Residency as an area of learning, which had given the psychologists the possibility of experiencing knowledge and daily situations found in SUS’ context, allowing mistakes, innovations and the construction and reformulation of ideas. There were discussed aspects related to the workload and the relationship between residents and health care team. The second article focused on the undergraduate training in psychology for working in primary health care. The results showed important movements of approximation between the psychology undergraduate courses and themes such as SUS, Community Health and Public Policies. In addition, it was pointed out to the importance of professors who are identified with the SUS’s proposals, as well as the value given to the discipline of groups as an important tool for the practice of psychologists in primary health care. The third article reported a significant change in the way that the psychology residents have conceived the psychologist’s role in primary health care. Such comprehension, not restricted to intra-individual aspects, drives to expanded and interdisciplinary practices. However, it was emphasized the charge for individual appointments and the large demand for the area of psychology. Based on the data obtained by the three articles, it was concluded that the Residency has enabled psychologists to experiment and create, which has been supporting the construction of practices more aligned to the principles of primary health care, overcoming the mere transposition of practices.